2013
DOI: 10.1007/s12040-013-0351-6
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal prediction of Indian summer monsoon: Sensitivity to persistent SST

Abstract: In the present study, the assessment of the Community Atmosphere Model (CAM) developed at National Centre for Atmospheric Research (NCAR) for seasonal forecasting of Indian Summer Monsoon (ISM) with different persistent SST is reported. Towards achieving the objective, 30-year model climatology has been generated using observed SST. Upon successful simulation of climatological features of ISM, the model is tested for the simulation of ISM 2011 in forecast mode. Experiments have been conducted in three differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The current study indicates inter-decadal spatial and temporal variability in the precipitation related to the monsoon onset in Pakistan. The results are consistent with the studies carried out around the globe indicating the changes in the summer monsoon rainfall in South Asia including Pakistan (Das et al 2013;Imran et al 2014;Latif and Syed 2015). Seasonal mean rainfall in south Asia shows interdecadal variability, particularly in terms of declining trend with frequently occurring deficiency in summer monsoon rainfall (Intergovernmental Panel on Climate Change 2014).…”
Section: Discussionsupporting
confidence: 89%
“…The current study indicates inter-decadal spatial and temporal variability in the precipitation related to the monsoon onset in Pakistan. The results are consistent with the studies carried out around the globe indicating the changes in the summer monsoon rainfall in South Asia including Pakistan (Das et al 2013;Imran et al 2014;Latif and Syed 2015). Seasonal mean rainfall in south Asia shows interdecadal variability, particularly in terms of declining trend with frequently occurring deficiency in summer monsoon rainfall (Intergovernmental Panel on Climate Change 2014).…”
Section: Discussionsupporting
confidence: 89%
“…(SST) and sea-ice concentrations are added with the latest persistent anomaly observed at the time the experiment was conducted. It has been assumed that the SST and sea-ice concentrations are persistent in nature over the forecasted time period; however, a sensitivity study of these persistent SSTs has also been done for a few monsoon years (DAS et al 2013).…”
Section: Seasonal Forecast Of Ism Rainfallmentioning
confidence: 99%
“…Presently, the atmosphere-land component of the CCSM model is used (DAS et al 2011) for experimental seasonal forecast at SAC. Every year upon completion of the summer monsoon season, the experimental seasonal and 30-day forecasts have been assessed with actual observations, and shortcomings in the forecast system have been identified for improvement in the subsequent year's forecasts (DAS et al 2012(DAS et al , 2013. On completion of 5 years since 2009, it is required to quantify the overall validation of the forecast system, and to assess the scope for further improvements of these experimental seasonal forecasts over time, if any.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sen Roy et al (2012) independently compared this rainfall product with Kalpana-1 GPI and TRMM Multisatellite Precipitation Analysis (TMPA) estimates and showed that IMSRA is closer to the TMPA estimate in terms of areal spread, geometric shape and location of rainfall areas, as compared to the GPI technique, and is capable of short-period rainfall estimation. This algorithm is also operational at the IMD since 2010 and is used for various agricultural and hydro-meteorological applications and verification of numerical model rainfall outputs Das et al, 2013;Mahesh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%